Clay mineralogy and shale instability: an alternative conceptual analysis. (April 2014) - Wilson, M. J .; Wilson, L.
Abstract: The instability of shales in drilled formations leads to serious operational problems with major economic consequences for petroleum exploration and production. It is generally agreed that the nature of the clay minerals in shale formations is a primary causative factor leading to their instability, although the exact mechanism involved is more debateable. Currently, the principal cause of shale instability is considered to be volume expansion following the osmotic swelling of Nasmectite. However, illitic and kaolinitic shales may also be unstable, so that interlayer expansion cannot therefore be considered as a universal causative mechanism of shale instability. This review considers alternative scenarios of shale instability where the major clay minerals are smectite, illite, mixed-layer illite-smectite (I/S) and kaolinite respectively. The influence of interacting factors that relate to shale clay mineralogy such as texture, structure and fabric are discussed, as are the pore size distribution and the nature of water in clays and shales and how these change with increasing depth of burial. It is found from the literature that the thickness of the diffuse double layer (DDL) of the aqueous solutions associated with the charged external surfaces of clay minerals is probably of the same order or even thicker than the sizes of a significant proportion of the pores found in shales. In these circumstances, overlap of the DDLs associated with exposed outer surfaces of clay minerals on opposing sides of micropores (<2 nm in diameter) and mesopores (2–50 nm in diameter) in a lithostatically compressed shale would bring about electrostatic repulsion and lead to increased pore/ hydration pressure in smectitic, illitic and even kaolinitic shales. This pressure would be inhibited by the use of more concentrated K-based fluids which effectively shrink the thickness of the DDL towards the clay mineral surfaces in the pore walls. The use of soluble polymers would also encapsulate these clay mineral surfaces and so inhibit their hydration. In this scenario, the locus of action with respect to shale instability and its inhibition is moved from the interlamellar space of the smectitic clays to the charged external surfaces of the various clay minerals bounding the walls of the shale pores.